Trickster's tale : hu yan zhuan. Volume 2 - Hontoku (Trickster's Tale: Hu Yan Zhuan, 2026)
"Sage Gaochun has been taken to the nether realm by his ex-lover, the demon Shui. In order to bring him back, Feijin meets with Gaochun's beloved younger brother, Gaoliu, to request his assistance. Unfortunately, when Gaochun was reincarnated in the mortal realm, it was into the royal family, so when Feijin approaches his brother, the second prince, he's quickly arrested as a suspicious person! It's then that a mysterious man who calls himself the emperor's secretary approaches, requesting that Feijin win...Gaochun's heart?!"--Amazon.com